The book of Al-Hisbah, the Abodes and What pertains to Imam as well as Other Issues Written by the Scholar and Judge: Abdullah bin Mohammed bin Abdullah bin Hamza bin Abi Najm (died in 647 A.H.) – A study and an investigation - Al-Qadi, Mohammed Yahya Ahmed Abdullah (Journal of Islamic Sciences, 2023)
This research dealt with Al-Hisbah issue (Al-Hisbah is an Arabic term means an act which is performed for the common good, or with the intention of seeking a reward from Allah), its provisions, the conditions of Al-Muhtasib, the three types of the abodes (Dar-ul-Islam, Dar-ul-Kufr as well as Dar-ul-Fisq ) as well as the provision related to each type of the abodes. The research aimed to study and investigate the issue of Al-Hisbah and also to introduce a scientific investigated material collected in one research and separated from other religious issues. The research methodology included the descriptive approach by which the researcher introduced the author briefly. And the investigation methodology included the description of the manuscript and comparing it to the copies, attributing the verses, authenticating Hadiths (Prophet Mohammed’s Sayings), tracking the statements as well as writing biographies about the celebrities. The researcher has reached a number of findings, the most important of which are: Al-Hisbah is a religious Wilayah (mandate) in which a person who has fulfilled its conditions shall set himself up for it and carry out its duties in case the judge or the leader is not available. Also, Al-Hisbah has no ruling after reaching Imamah (the authority). In addition, Al-Muhtasib performs specific responsibilities including enjoining good, forbidding what is wrong, protecting the incest, guarding people’s chastity as well as supervising the markets. What is more, one of the provisions of the abode of war (Dar-ul-harb) and the abode of depravity and (Dar-ul-fisq) is that Muslims shall not live there. The research recommends to spread the importance of Al-Hisbah and to distinguish between the abode of Islam and the other abodes.
Keywords: Hisba; Al-Muhtasib; Dar Al-islam; Dar Al-Kufr; Dar Al-Fesg